AUTOMAÇÃO NA QUANTIFICAÇÃO DE CABOS ELETRICOS EM SOFTWARE PARAMÉTRICO BASEADO EM OBJETOS 3D - Dantas Filho, João Bosco P.; Andrade, George de Francisco dos Santos; Evangelista, Artur de Almeida; Angelim, Bruno Maciel; Barros Neto, José (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
A set of technologies, processes, policies and especially BIM skills are required to enable BIM use: extraction of quantities. However, despite the need for this knowledge, obstacles arise to challenge designers. Electrical cables are not modeled, but only treated as annotations in conduits, and so it is not possible to extract quantities of non-modeled elements. The repetitive process automation is able to help the modeling of construction information and serve for circumventing obstacles in the work routine. The objective of this work is to explore the creation of routines of automation to correlate data of electrical cables with length of conduits to enable the extraction of cables quantities. The methodology is qualitative, and the research strategy is action research. Using Dynamo as a design information processing platform enabled the extraction of cabling quantities from the BIM model. It is observed that the challenges of innovation occur in the daily routine of professionals who need new skills to express creativity and innovation. As a contribution, the research exposes a limitation of Revit specifically on electrical projects that software developers can invest in enhancements.